Inter-cell Interference Mitigation through Flexible Resource Reuse, LP-OFDM and Coordination techniques for LTE Advanced in Dense Urban Area - Balboul Younes; Najiba El Amrani El Idrissi (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
The inter-cell interference problem is a key issue in LTE Advanced system especially in dense urban environments. This paper present a new inter-cell interference reduction technique for LTE Advanced downlink system in dense urban area based on a new coordination algorithm with the use of linear precoding OFDM, coordination between cells and power management techniques. The objective of our new technique is to improve cell edge and centre capacity in LTE Advanced downlink system. For this purpose, we prove with real time simulations using Matlab that the S.F.R and P.F.R scheme with our algorithm is a good candidate to enhance the average cell capacity and edge user experience, without sacrificing the average cell throughput.